INVESTIGATION THE RELATIONSHIP BETWEEN HUMAN RESOURCE MANAGEMENT PRACTICES AND FIRM'S FINANCE PERFORMANCE - Sojka, Ladislav (European Scientific Journal, ESJ, 2015)
This paper briefly describes the practices of human resource management as an idiosyncratic source of competitive advantage. It discusses various authors' views on the relationship between human resource management practices and firm's economic performance. The paper also discusses the complexity of studying the said relationship. It concludes that despite statistical analysis revealing a positive correlation, the causality of the effect was not proven. The experimental research studies the link between human resource management practices and economic performance on a sample of 102 organizations, studying basic management practices, such are strategy, organizational structure, corporate culture and operational management. The research reveals a positive correlation between HR practices and economic performance, but only if the management practices were provided on average or above-average levels. For other practices, the study showed evidence of a statistically relevant correlation only in the case of remuneration.